DOCTOR INERTNESS AS A FACTOR DISTURBING EFFECTIVE TREATMENT OF CARDIOVASCULAR DISEASES - E. V. Minakov; R. A. Khokhlov; G. I. Furmenko; N. M. Akhmedzhanov (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate factors contributing to development of inertness in doctors of the primary care which treat and follow-up patients with cardiovascular diseases (CVD).Material and methods. The anonymous poll was carried out among 184 primary care physicians. The questionnaire included information about sex, age, time and conditions of work, established stereotype of practice, knowledge of current guidelines on CVD treatment. The study was one-stage with usage of questionnaire.Results. High prevalence of inertness was observed among physicians. Only 43 (26,4%) of doctors had active stereotypes of practice, which prevent inertness. These physicians have more often post-graduate specialization, read international guidelines, foreign and web-journals, evaluate higher non-drug approaches to prevention and therapy and they more often initiate long-term patient observation.Conclusion. Inertness is common behavior feature among primary care. The main reasons of this inertness are insufficient knowledge of modern guidelines on CVD treatment and lack of skills on its practical usage.